Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Differential response of denitrifying and diazotrophic soil populations to short and long-term exposure of glyphosate and atrazine - L. Ferrando; M. I. Bellini; A. Fernández-Scavino (Environmental Sustainability, 2023)

Vacchi's palatal organ: a widespread trait in Holocephali - B. Finucci; L. Gallus; A. Amaroli; S. Candiani; M. Rottigni; M. A. Masini; S. Ferrando (Journal of Fish Biology, 2018)
A palatal organ, possibly used for food sorting and processing, has previously been identified among the vomerine toothplates of the chimaeroid Chimaera monstrosa . In this study, the palatal organ was described in six additional species, confirming it is a widespread trait among holocephalans. It is proposed that this palatal structure, which appears to differ in shape according to each chimaeroid's degree of durophagy and is not homologous to the palatal structure described in teleosts, be hereby referred to as Vacchi's organ.

Gross morphology and histology of the olfactory organ of the Greenland shark Somniosus microcephalus - S. Ferrando; L. Gallus; L. Ghigliotti; M. Vacchi; J. Nielsen; J. S. Christiansen; E. Pisano (Polar Biology, 2016)

Taxonomic and Functional Resilience of Grasshoppers (Orthoptera, Caelifera) to Fire in South Brazilian Grasslands - C P R Ferrando; L R Podgaiski; M K M Costa; M D S Mendonça (Neotropical Entomology, 2016)

Fragments of the Western Alpine Chain as Historic Ornamental Stones in Turin (Italy): Enhancement of Urban Geological Heritage through Geotourism - A. Borghi; A. d’Atri; L. Martire; D. Castelli; E. Costa; G. Dino; S. E. Favero Longo; S. Ferrando; L. M. Gallo; M. Giardino; C. Groppo; R. Piervittori; et al. (Geoheritage, 2014)

The training-induced changes on automatism, conduction and myocardial refractoriness are not mediated by parasympathetic postganglionic neurons activity - M. Zarzoso; L. Such-Miquel; G. Parra; L. Brines-Ferrando; L. Such; F. J. Chorro; J. Guerrero; A. Guill; J. E. O’Connor; A. Alberola (European Journal of Applied Physiology, 2012)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

Na + /K + ATPase immunoreactivity in olfactory epithelium of small‐spotted catshark Scyliorhinus canicula (L.): possible presence of ion exchanging cells? - S. Ferrando; M. Bottaro; L. Gallus; L. Girosi; M. Vacchi; G. Tagliafierro (Journal of Fish Biology, 2006)
Na + /K + ATPase immunoreactivity in olfactory epithelium of Scyliorhinus canicula was localized in well featured light large cells. It was distributed in the basolateral membranes as reported in the literature for typical ion exchanging cells.